Developing Guidance and Counseling Administration Management Information System “Simas BK” to Increase the Accountability of Vocational Education School Counselors in Yogyakarta City - Faiz Mudhokhi; Sigit Sanyata (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The success of guidance and counseling services in schools largely depends on School Counselors’ managerial abilities in planning, organizing, and evaluating services. However, many School Counselors are burdened with additional tasks beyond their main responsibilities, including administrative duties that are still handled manually, hindering optimal service delivery. Therefore, an information system is needed to simplify administrative tasks and reduce barriers to work. This study aims to examine: 1) the feasibility of an administrative information system in improving the accountability of School Counselors, 2) the practicality of an administrative information system in improving the accountability of School Counselors, and 3) the effectiveness of an administrative information system in improving the accountability of School Counselors. Using the Borg & Gall R&D model, the study involved vocational high school School Counselors and employed an administrative information system scale as the research instrument. The results showed that the system was deemed feasible by expert validation, practical by School Counselors, and effective in enhancing accountability. In the long term, SIMAS BK has the potential to be broadly implemented and integrated into national education systems to support data-driven counseling services. Keywords: administrative, information system, accountability